Coping mechanisms and academic performance of medical technology students of National University-Manila in online learning - Alcantara, Gerard Peter A.; Cabatuan, Marianne Blythe T.; De Guzman, Rica Marie; Medua, May Ann B.; Ramirez, Joanna Marie A. (Manila : National University, 2023)
The findings demonstrated that the type and amount of online learning challenges faced by college students varied in terms and extent.
Chapter 1. Introduction -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary of Findings, Conclusions and Recommendation -- References.
Includes bibliographical references.